Mid-term results of a physiotherapist-led Ponseti service for the management of non-idiopathic and idiopathic clubfoot. (June 2015) - Dunkley, Mia; Gelfer, Yael; Jackson, Debbie; Parnell, Evette; Armstong, Jennifer; Rafter, Cristina; Eastwood, Deborah M.
Background: The Ponseti method is the preferred treatment for idiopathic clubfoot. Although popularised by orthopaedic surgeons it has expanded to physiotherapists and other health practitioners. This study reviews the results of a physiotherapist-led Ponseti service for idiopathic and non-idiopathic clubfeet and compares these results with those reported by other groups. Method: A prospective cohort of clubfeet (2005–2012) with a minimum 2-year follow-up after correction was reviewed. Physiotherapists treated 91 children—41 patients (69 feet) had non-idiopathic deformities and 50 children (77 feet) were idiopathic. Objective outcomes were evaluated and compared to results from other groups managing similar patient cohorts. Results: The mean follow-up was 4.6 years (range 2–8.3 years) for both groups. The non-idiopathic group required a median of 7 casts to correct the clubfoot deformity with an 83 % tenotomy rate compared to a median of 5 casts for the idiopathic group with a 63 % tenotomy rate. Initial correction was achieved in 96 % of non-idiopathic feet and in 100 % of idiopathic feet. Recurrence requiring additional treatment was higher in the non-idiopathic group with 40 % of patients (36 % of feet) sustaining a relapse as opposed to 8 % (6 % feet) in the idiopathic group. Surgery was required in 26 % of relapsed non-idiopathic feet and 6 % of idiopathic. Conclusions: Although Ponseti treatment was not as successful in non-idiopathic feet as in idiopathic feet, deformity correction was achieved and maintained in the mid-term for the majority of feet. These results compare favourably to other specialist orthopaedic-based services for Ponseti management of non-idiopathic clubfeet. Level of evidence: Prognostic Level III.